2020
DOI: 10.1002/cam4.3055
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gap: Contribution of surgical best practices to outcome differences between high‐ and low‐volume centers for lung cancer resection

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Improved outcomes in academic settings are generally attributed to higher compliance with clinical practice guidelines, 37 use of best surgical practices, and high patient volumes. 39 However, in a comparison of clinical outcomes after NSCLC resection between small-volume and high-volume practices, von Itstein recently demonstrated that although OS was improved at high-volume centers, when controlling for best surgical practices, there was no difference between high-volume and low-volume practices. 39 Consistent with these findings, our study strongly suggests that survival outcome did not differ between patients treated at an academic medical center and those treated at a community oncology practice, when reviewed by the UK MCC-MTB.…”
Section: Discussionmentioning
confidence: 99%
“…Improved outcomes in academic settings are generally attributed to higher compliance with clinical practice guidelines, 37 use of best surgical practices, and high patient volumes. 39 However, in a comparison of clinical outcomes after NSCLC resection between small-volume and high-volume practices, von Itstein recently demonstrated that although OS was improved at high-volume centers, when controlling for best surgical practices, there was no difference between high-volume and low-volume practices. 39 Consistent with these findings, our study strongly suggests that survival outcome did not differ between patients treated at an academic medical center and those treated at a community oncology practice, when reviewed by the UK MCC-MTB.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the influence of facility volume on short‐ or long‐term patient outcomes (i.e., volume–outcomes relationship) is an important endeavor that can lead to better delivery of quality care and more centralized cancer treatment in the future 14,15 . Although recent studies have demonstrated improved survival with increasing hospital volume in a variety of cancers including lung cancer, 16 Hodgkin lymphoma, 17 Merkel cell carcinoma, 18 meningioma, 19 and malignant bone tumors, 20 a thorough investigation regarding NPC is needed. Herein, this study investigates a large US‐based patient population from the National Cancer Database (NCDB) to elucidate the facility‐volume–outcomes relationships in patients with NPC.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a higher case volume hospital was associated with a lower prevalence of both postoperative fatal respiratory events and in-hospital mortality. For postoperative patient management, it is more likely that high case volume hospitals with a large number of specialized medical staff and better 24-hour care enable the prevention of fatal respiratory events through faster and adequate diagnosis and intervention (22,24). Wang et al reported that pulmonary complications after lung resection were associated with prolonged LOS and increased hospitalization costs (25).…”
Section: Discussionmentioning
confidence: 99%
“…This result may be related to the higher prevalence of postoperative fatal respiratory events in the low case volume center, as shown in Table 2 . However, a previous study reported that the impact of hospital case volume on clinical outcomes was not fixed and might be improved by education, systematic, and faculty improvement ( 22 ). In a previous study conducted in Taiwan, hospital case volume alone was not a significant predictor of in-hospital mortality following lung cancer surgery after adjusting for patient, surgeon, and hospital characteristics ( 23 ).…”
Section: Discussionmentioning
confidence: 99%